2018
DOI: 10.1016/j.bjpt.2018.02.006
|View full text |Cite|
|
Sign up to set email alerts
|

Reference values for muscle strength: a systematic review with a descriptive meta-analysis

Abstract: Most of the included studies had adequate methodological quality. The meta-analysis provided reference values for the isometric strength of 14 appendicular muscle groups of the dominant/non-dominant sides, measured with dynamometers/myometers, of men/women, of adults/elderly. These data may be used to interpret the results of the evaluations and establish appropriate treatment goals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 71 publications
1
29
1
7
Order By: Relevance
“…Hip abductor and hip extensor muscles can work together to affect postural reactions and are important for standing and walking [34]. A recent systematic review [23] highlighted a study by Andews at al [35] that utilised HHD to test lower-limb strength for males and females aged 50-79 years. Participant positioning for hip abduction strength testing was similar to the method we employed; however, matching for sex-and age-decade, our muscle strength values were approximately one-third lower than their maximum values for dominant or non-dominant sides.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hip abductor and hip extensor muscles can work together to affect postural reactions and are important for standing and walking [34]. A recent systematic review [23] highlighted a study by Andews at al [35] that utilised HHD to test lower-limb strength for males and females aged 50-79 years. Participant positioning for hip abduction strength testing was similar to the method we employed; however, matching for sex-and age-decade, our muscle strength values were approximately one-third lower than their maximum values for dominant or non-dominant sides.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, assessment of lower limb strength offers an alternative when handgrip strength is not feasible due to hand disability. A role for measuring lower-limb muscle strength in geriatric assessment needs the support of appropriate normative data for quantifying deficits, but there are few published for the lower-limb [23].…”
Section: Introductionmentioning
confidence: 99%
“…In the obese group, the values were 256.2 N and 261.1 N, respectively. In a literature review, Ben ca et al [42] describes hip abductor muscle strength values, in individuals between 50 and 59 years old, as being 208.12 N for dominant limb and 203.27 N for non-dominant limb in women, and 305.97 N for dominant limb and 298.49 N for non-dominant limb in men. In the present study, this variation in the measurements can be explained by the age differences between the analyzed samples, gender variations, and differences related to the measurement technique.…”
Section: Discussionmentioning
confidence: 99%
“…In a literature review, Ben ca et al [38] reported the hip abductor muscle strength values in individuals aged between 50 and 59 years old to be 208.12 N for the dominant limb and 203.27 N for the nondominant limb in women and 305.97 N for the dominant limb and 298.49 N for non-dominant limbs in men. In the present study, this variation in the measurements can be explained by the age differences among the individuals included in the analysis, differences in sex, and differences related to the measurement technique.…”
Section: Discussionmentioning
confidence: 99%
“…Obese individuals who were beginning ambulatory follow-ups at the Obesity and Bariatric Surgery Service in the Western Paraná University Hospital (Cascavel, Paraná, Brazil) were included in the study. These individuals were of both sexes, were aged 20 to 60 years old, had grade II and III obesity, and had a body mass index (BMI) higher than 35 kg/m 2 [37,38]. The exclusion criteria were pregnancy, an orthopaedic disease of the lower limbs, locomotor system pain or sequelae, paresthesia or weakness in the lower limbs, orthostatic or walking pain, heart disease, or other diseases with restricted functional capacity.…”
Section: Methodsmentioning
confidence: 99%